Pre-cooling for performance in the tropics - Brearley, M.; Finn, J. P. (Sportscience, 2003)
Pre-cooling improves power output by up to 7% in continuous exercise lasting less than an hour in tropical conditions. Although there are various cooling methods, practical and effective modes with suitable durations are yet to be determined for intermittent or more prolonged exercise. Research factoring in solar radiation and any placebo effect is necessary to determine the optimal strategies of pre-cooling for tropical conditions.